De Invloed van bedrijfsstrategieën op de prestaties van kleine, familiale ondernemingen: De casus steen- en buizenbakkerij Dumoulin in Langemark en Wijtschate, ca. 1922-1981 - Descheemaeker, Kim (TSEG - The Low Countries Journal of Social and Economic History, 2021)
The impact of compagny stragegies on the performance of small family compagnies. Dumoulin brick and pipe factory in Langemark and Wijtschate (Belgium), c. 1922-1981.The case of the Dumoulin brick and pipe factory (c. 1922-1981) in Langemark and Wijtschate in the southern Westhoek (Belgium) can be regarded as a typical example of a small, family-owned, West Flemish company that tried to survive in a turbulent business environment. In the twentieth century, the ceramic sector was characterized by large-scale technological changes and a rearrangement of the industrial landscape. This article reconstructs and analyzes the life cycle of the Dumoulin brick and pipe factory. The use of an explicit theoretical framework and the regional focus contribute to the international historiography of small and medium-sized enterprises and family businesses, as well as to the socio-economic history of West Flanders.